The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/bcpt.13696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin on ovarian function and regulation of the ovarian PI3K/Akt/FoxO3a signalling pathway and oxidative stress in a rat model of cyclophosphamide‐induced premature ovarian failure

Abstract: To investigate the ability of quercetin to improve ovarian function and inhibit ovarian oxidative stress through the PI3K/Akt/FoxO3a signalling pathway in a rat model of premature ovarian failure (POF), we constructed a POF rat model with cyclophosphamide (CTX) and treated it with quercetin. Haematoxylin and eosin staining (H&E staining) was used to observe the morphological changes of the ovaries. The serum levels of AMH, E2, FSH, SOD, GSH‐Px and MDA were determined by enzyme‐linked immunosorbent assays. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Its main function is to maintain the function of the female reproductive system and the secretion of hormones [ 23 ]. The imbalance of free radical metabolism caused by endemic fluorosis and the damage of organ function caused by the accumulation of a large number of oxidative stress products have always been a hot issue for researchers [ 23 ]. Oxidative stress injury will promote the production of inflammatory factors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its main function is to maintain the function of the female reproductive system and the secretion of hormones [ 23 ]. The imbalance of free radical metabolism caused by endemic fluorosis and the damage of organ function caused by the accumulation of a large number of oxidative stress products have always been a hot issue for researchers [ 23 ]. Oxidative stress injury will promote the production of inflammatory factors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 can promote the secretion of proinflammatory cytokines, aggravate cell damage, and induce cell death [32,33]. Inhibiting NLRP3 inflammatory signal can reduce inflammatory response and protect tissues, promote the release of anti-inflammatory cytokine IL-10 and proinflammatory cytokine IL-21 levels in serum, improve the inflammatory response of ovary, and reduce the inflammatory injury of follicle and the decline of ovarian reserve function [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. This study showed that the HUCMSCs suppressed NOX4, NLRP3, and GSDMD protein expression levels in the in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…After carefully reviewing the full-text review ,13 studies were excluded due to the discrepancy of inclusion and exclusion criteria mentioned above. 14 studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22] were nally selected for meta-analysis. A PRISMA ow diagram describing the process of literature search and selection is presented in Fig.…”
Section: Results Of Articles Retrievalmentioning
confidence: 99%
“…Furthermore, quercetin is also a class of flavonoid natural compounds with anti-inflammatory, antioxidant, anti-obesity and anti-cancer properties. Studies have shown that quercetin can intervene in the development of PCOS, EMs and POI in a multi-targeted and multi-pathway manner (Park et al, 2019;Chen et al, 2022;Zheng et al, 2022), while quercetin supplementation significantly increased the relative abundance of Akkermansia and reduced the ratio of F/B in obese mice (Tan et al, 2021), improved LPS-induced inflammatory damage (Bian et al, 2018), maintained glucolipid metabolic and promoting the production of SCFAs to enhance insulin sensitivity and improve the inflammatory response. Therefore, we hypothesize that quercetin may ameliorate reproductive endocrine disorders by reshaping the structure of the intestinal flora and increasing the content of SCFAs.…”
Section: Active Ingredients Of Chinese Herbal Medicinesmentioning
confidence: 99%